2015
DOI: 10.2139/ssrn.2712327
|View full text |Cite
|
Sign up to set email alerts
|

Student Employment: Advantage or Handicap for Academic Achievement?

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Even though there are factors that affect learners' performance, some learners also contribute to poor performance. Lack of time management affects learners' academic achievement (Sprietsma, 2015). Exploring psychological factors of learners found that time management has an impact on a learners' performance because learners do not give themselves enough time to do their school work.…”
Section: Grade 12 Physical Science Learners' Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Even though there are factors that affect learners' performance, some learners also contribute to poor performance. Lack of time management affects learners' academic achievement (Sprietsma, 2015). Exploring psychological factors of learners found that time management has an impact on a learners' performance because learners do not give themselves enough time to do their school work.…”
Section: Grade 12 Physical Science Learners' Performancementioning
confidence: 99%
“…Researchers indicated that the employment of learners is a negative factor in their academic achievement (Sprietsma, 2015). Some learners are employed as casual workers in different shops.…”
Section: Grade 12 Physical Science Learners' Performancementioning
confidence: 99%
“…youth unemployment rate, as the instrumental variable (see Rothstein, 2007;Beffy et al, 2013;Holford, 2020;Lee & Orazem, 2010). Other studies use child labor laws (Tyler, 2003;Apel et al, 2008), the proportion of unearned income (DeSimone, 2006), paternal schooling (DeSimone, 2008), socio-economic status of the family (Simon et al, 2017), amount of financial aid students obtain (Sprietsma, 2015), or the variation in area house prices (Darolia, 2014) as their instrumental variables. Related to the instrumental variable estimation, some researchers rely on the simultaneous equation modeling (Parent, 2006).…”
Section: Structural Variationmentioning
confidence: 99%
“…Percentages of male and female students employed during studies. Data obtained from [10][11][12][13][14].…”
Section: Gendermentioning
confidence: 99%
“…Students working as an assistant in research and private lessons/coaching of pupils are most likely to choose employment relevant to their major (61% and 60%). Students working as an assistant in a firm have the next highest tendency to choose major-related employment (35%), but students only helping out in a firm have the lowest tendency to choose major-related employment (6%) [13]. Paid internship is one typical type of major-related employment.…”
Section: Major Relevancementioning
confidence: 99%